PENGARUH PERSEPSI KEADILAN PAJAK, EFEKTIVITAS SISTEM PERPAJAKAN, KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WPOP SAMARINDA ILIR - Anggreani, Nur Rahmah; Rantelangi , Cornelius (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to obtain evidence that the influence of perceptions of tax fairness, the effectiveness of the tax system, and the quality of fiscus services have a significant and positive effect on individual taxpayer compliance at KPP Pratama Samarinda Ilir. This type of research is quantitative research with primary data sources. Determination of the sample using purposive sampling method with a total of 100 respondents amounting to taxpayers freelancers. Data analysis from this study used the Structure Equation Modeling-Partial Least Square (SEM-PLS) method assisted by SmartPLS version 4 program. The result of this study indicate that the influence of perceptions of tax fairness, the effectiveness of the tax system, and the quality of fiscus services have a significant and positive effect on individual taxpayer compliance